A Critical Analysis of Efficacy of the Prevention of Electronic Crimes Act, 2016: Irritants and Remedies - Shah, Syed Khizar Ali (Journal of Pakistan Administration, 2024)
Cyber technologies are rapidly proliferating in Pakistan manifesting their pros and cons on the Pakistani governance system and society necessitating a new social contract between the state and citizenry. Prevention of Electronic Crimes Act (PECA, 2016) is an attempt to define the contours of this new state-citizen relationship in the cyberworld. However, PECA’s purported relevance has been submerged under the civil society’s backlash at the controversial enforcement of PECA, 2016 and the unabated deluge of cybercrimes. A comparative analysis of India’s response mechanisms against the ever-evolving challenge of cybercrimes can help policy makers in Pakistan to tackle the issue effectively. Moving forward, Pakistan may have to rectify its policy orientation from being security centric to citizen centric by introducing humane amendments in PECA, 2016 and make prudent investments in capacity building of its citizens and state agencies.
Keywords: PECA; 2016; cybercrimes; digital rights